A Comparative Analysis between a SIRD Compartmental Model and the Richards Growth Model - Macêdo, A. M. S.; Brum, A. A.; Duarte-Filho, G. C.; Almeida, F. A. G.; Ospina, R.; Vasconcelos, G. L. (Trends in Computational and Applied Mathematics, 2021)
We propose a compartmental SIRD model with time-dependent parameters that can be used to give epidemiological interpretations to the phenomenological parameters of the Richards growth model. We illustrate the use of the map between these two models by fitting the fatality curves of the COVID-19 epidemic data in Italy, Germany, Sweden, Netherlands, Cuba, and Japan, up to July 30, 2020.